(untitled) (Applied Biological Research, 2012)
Field experiments were conducted during rabi 2007-08, 2008-09 and 2009-10 at PRSS, Samba, SKUAST-Jammu in Inceptisols to find out the effects of seed priming, sowing depth and seed treatment with fungicide on chickpea. The treatments consisted of seed priming (seed soaking in water for 8 h), sowing depth (7.5 and 10 cm) and seed treatment with carbendazim 50WP. The observations on plant height, nodule dry weight, seed index, dry matter accumulation, yield and yield attributes of chickpea were recorded. The results revealed that the growth parameters of chickpea were significantly affected by seed priming, sowing depth and seed treatment with fungicide. Dry matter accumulation, yield and yield attributes differed significantly with seed priming and sowing depth. Plant height of chickpea showed significantly highly correlation with nodule dry weight accumulation which, in turn, enhanced the seed and biological yield with the accuracy of 87%.